Vol. 2422 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2021): International Youth Scientific Conference, 20–22 April 2021, Tomsk, Russia; AIP Conference Proceedings - Kuznetsov G. V. Geny Vladimirovich; Feoktistov D. V. Dmitriy Vladimirovich; Orlova E. G. Evgeniya Georgievna (2021, 2021)
Title screen